The SWI/SNF-Related, Matrix Associated, Actin-Dependent Regulator of Chromatin A4 Core Complex Represses Respiratory Syncytial Virus-Induced Syncytia Formation and Subepithelial Myofibroblast Transition - Xu, Xiaofang; Qiao, Dianhua; Dong, Chenyang; Mann, Morgan; Garofalo, Roberto P.; Keles, Sunduz; Brasier, Allan R. (Frontiers in Immunology, 2021)
Epigenetics plays an important role in the priming the dynamic response of airway epithelial cells to infectious and environmental stressors. Here, we examine the epigenetic role of the SWI/SNF Related, Matrix Associated, Actin Dependent Regulator of Chromatin A4 (SMARCA4) in the epithelial response to RSV infection. Depletion of SMARCA4 destabilized the abundance of the SMARCE1/ARID1A SWI/SNF subunits, disrupting the innate response and activating a partial epithelial mesenchymal transition (pEMT) program. Assaying SMARCA4 complex-regulated open chromatin domains by transposase cleavage -next generation sequencing (ATAC-Seq), we observed that the majority of cleavage sites in uninfected cells have reduced chromatin accessibility. Paradoxically, SMARCA4 complex-depleted cells showed enhanced RSV-inducible chromatin opening in the EMT pathway genes, MMP9, SNAI1/2, VIM and CDH2. Focusing on the key MMP9 regulator, we observed that SMARCA4 complex depletion reduced basal BRD4 and RNA Polymerase II binding, but enhanced BRD4/Pol II binding in response to RSV infection. In addition, we observed that MMP9 secretion in SMARCA4 complex deficient cells contributes to pEMT, cellular fusion (syncytia) and subepithelial myofibroblast transition. We conclude the SMARCA4 complex is a transcriptional repressor of a “default” pEMT program and affects the dynamic response of the small airway epithelial cell via paracrine MMP9 activity.